Sadzawka Bethesda (J 5, 2) w patrystycznej i współczesnej egzegezie - Górka, Bogusław (Vox Patrum, 1999)
The second verse of the fifth chapter of the Gospel according to John is a true crux exegetarum indeed. Nobody may feel responsible for the interpretation of the meaning of this passage since any translation is merely an interpretation of the original represented by the preference of the single translator.